Activity Ratio Analysis to Measure the Level of Financial Effectiveness of PT Kalbe Farma Tbk, 2020-2023 Period - Lillian Sonya Loppies (International Journal Business, Management and Innovation Review, 2024)
Financial analysis using the Du Pont System combines activity ratios and profit margins on sales, and how these ratios interact with each other in determining profitability and assets. The approach with the Du Pont System Financial Analysis is one of the relevant financial performance measurement tools used to see the extent of the company's effectiveness in taking over the investment made by the company or ROI (Retrun On Invesment). The purpose of this research is to analyze the financial performance of PT Telkom Indonesia Tbk by using the dupont system method.The type of research used is quantitative. The type of data used in this research is secondary data taken from the financial statements of PT Telkom Indonesia in 2018-2022. The data analysis technique used in this study is to calculate NPM, TATO, ROI, EM, and ROE. The results of this study are the financial performance of PT Telkom Indonesia Tbk which is assessed using the DuPont System method can still be said to be not optimal or tends to experience fluctuating conditions. This is because the company in managing assets and capital as measured by ROE DuPont System is said to tend to experience a fluctuating state even though in certain years it has increased but is still below the BUMN standard for ROE.